Multiculturalism in the United States of America: Amish Community as a Model (The International Journal of Educational Sciences and Arts, 2025)
Since its founddadion, The USA emerged as a Pluralisties society, whether religiously or culturally, and other. manifestations of diversity that were the result of immigration to the New World for several reasons, foremost of which were religious reasons, so the United States of America embraces groups of diverse ethnic and cultural origins coexisting side by side, and among these groups that immigrated to the United States to escape religious persecution is the Amish sect. The Successive migrations from several nations and cultures led to  political, economic turmoil, in addition, toother so on As a result of this cultural diversity and in an attempt to find common ground for this multiculturalism, the Amish community was able to maintain its social fabric away from all the challenges that formed the demographics of the United States of America, as there are many challenges it faces in terms of organizing its life according to its beliefs, which sometimes pushes it to withdraw from society in order to maintain the cohesion of its society.
Keywords: Multiculturalism; Religion; Amish; United States of America